IMPLEMENTATION OF TEACHERS’ PEDAGOGICAL COMPETENCIES IN IMPROVING STUDENTS’ LEARNING MOTIVATION AT MTS DAARUL MA’ARIF PASAWAHAN - Kamilah, Hanna; Sofa Latifah, Siti; Wulandari, Dyah (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to analyse the implementation of teacher competencies in improving students’ learning motivation at MTs Daarul Ma’arif Pasawahan. A teacher’s professionalism is measured not only by mastery of the subject matter, but also by pedagogical, social, and personal skills. This research employs a qualitative approach using interviews, observations, and documentation as methods of data collection. The findings reveal that: (1) The development of teaching materials at MTs Daarul Ma’arif begins with diagnosing each student’s learning style tendencies, although in practice this has not been optimally implemented. (2) Teachers at MTs Daarul Ma’arif have not fully implemented the curriculum as expected. One of the main obstacles is the lack of training and mentoring for teachers in understanding and applying the principles of the Merdeka Curriculum. This has led to a gap between the ideal concept of the curriculum and the reality of classroom learning. (3) The learning process at MTs Daarul Ma’arif has not yet fully utilized technology-based learning media. Teaching is still dominated by conventional media such as books and blackboards. Based on these findings, the researcher provides several recommendations to improve the quality of learning and student motivation, namely through continuous competency development so that teachers can optimize the implementation of innovative teaching practices aligned with technological advancements.